CO2/N2 separation properties of polyimide-based mixed-matrix membranes comprising UiO-66 with various functionalities - Chuah, Chong Yang (2021)
Nanocrystalline UiO-66 and its derivatives (containing -NH2, -Br, -(OH)2) were developed via pre-synthetic functionalization and incorporated into a polyimide membrane to develop a mixed-matrix membrane (MMM) for CO2/N2 separation. Incorporation of the non-functionalized UiO-66 nanocrystals into the polyimide membrane successfully improved CO2 permeability, with a slight decrease in CO2/N2 selectivity, owing to its large accessible surface area. The addition of other functional groups further improved the CO2/N2 selectivity of the polymeric membrane, with UiO-66-NH2, UiO-66-Br, and UiO-66-(OH)2 demonstrating improvements of 12%, 4%, and 17%, respectively. Further evaluation by solubility-diffusivity analysis revealed that the functionalized UiO-66 in MMMs can effectively increase CO2 diffusivity while suppressing N2 sorption, thus, resulting in improved CO2/N2 selectivity. Such results imply that the structural tuning of UiO-66 by the incorporation of various functional groups is an effective strategy to improve the CO2 separation performance of MMMs.